The potential lipolysis function of musclin and its mRNA expression both in Pig adipose tissue and primary adipocyte - Chao Sun; Yongjia Peng, Dongfeng Jiang; Zhongpin Zhang (African Journal of Pig Farming, 2016)
Musclin is a newly discovered factor and its functions remain to be defined. This study investigated the tissue expression pattern of musclin gene and its potential effect on lipid metabolism. Musclin mRNA levels in adipose, muscle tissues and primary adipocytes were examined by quantitative PCR. The musclin gene expression in adult adipose tissue was significantly higher than that in muscle (p < 0.05), and its expression in young adipose tissue was higher than old one. We further found that in adipose tissue, the expression level of musclin had a negative correlation with FAS gene (p = 0.01), and positive correlation with PPAR gene (p < 0.05). In adipocyte, the expression level of musclin gene had a positive correlation with LPL gene (p < 0.01). Our results suggested that musclin is a potential factor that might play an important role in the regulation of adipogenesis.